Cooperation between vocational high schools and world of work: A case study at SMK Taman Karya Madya Tamansiswa - Muh. Juandi Arif Baitullah; Wagiran Wagiran (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2019)
The purpose of this study was to find out: the school strategy, procedure, forms, and evaluation to cooperate with the world of work. The type of research is qualitative with a case study approach. The subjects in this study were the head of the department, the chairman of the special job fairs, the vice-principal of public relations, the vice-principal of curriculum, the head of competence skills, and industry that were in cooperation with the school. The methods of collecting the data were in-depth interviews and documentation. The results show that: (1) the school strategy in cooperation with industry began with industry visits, requesting permission to do industrial practice, good communication, submitting proposals related to school potential in the form of profiles, being active in participating in school promotions, utilizing the role of industry as a guest teacher, being a pre-service place and outsourcing to industry; (2) the cooperation procedure analyzed the community, in this case, the world of work, established communication, and Involved world of work; (3) the forms of cooperation were the training of skills improvement in the field of science and technology, exchange of information, curriculum synchronization and development, implementation of internships, implementation of competency and certification tests, industry visits, industrial work practices, special job fairs, recruitment; (4) the evaluation of management in the implementation of the cooperation was included in the